Russian Strategy for Eurasian Integration: Key Elements, Determinants and Prospects for Development - D. S. Alekseev (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
Eurasia is gradually turning into the point of intersection of various longterm political and economic initiatives undertaken by the leading actors of contemporary international relations, including the Russian Federation, the European Union, the United States and the People’s Republic of China. This trend compounded by a complicated dynamics of integration and disintegration processes in the post-Soviet states further exacerbates tensions in the region, already fraught with conflict. It also poses additional obstacles to the projects of Eurasian integration, promoted by the Russian Federation. In order to provide a better understanding of the specificities and prospects of Russia’s initiatives, the paper examines the origins and the evolution of the Russian strategy of Eurasian integration, and identifies its key elements. The author concludes that fundamental principles of the Russian strategy for reshaping the post-Soviet states have been laid down during the presidency of B.N. Yeltsin and were merely adjusted to meet certain political, social and economic changes both in Russia and abroad. These principles include: 1) commitment to the idea of a multipolar world; 2) creation of supranational Eurasian economic institutions to multiply the economic potential of member-states; 3) prevention of a change of political regimes in neighboring countries if they can bring to power anti-Russian groups; 4) establishment of closer links with China, especially on political, economic and security issues; 5) formation of a new center of political gravity in Eurasia through expanding the capacities of regional political and military organizations which would complement integration processes and ensure regional security. The paper shows that amid growing international tensions in the second half of 2010s the Russian integration initiatives have become increasingly focused on geostrategic, political and military issues. In that regard, the author concludes that, although the development of the Eurasian integration projects enables a wide range of horizontal and vertical economic linkages between the Eurasian Economic Union (EAEU) memberstates, overtly competitive nature of both the Russian and the Western states’ strategies increases the conflict potential of the region. In the absence of alternative approaches, this conflict could not only become a potential source of new tensions between Russia and the West, but also threatens to reverse the current integration processes within the EAEU. The author emphasizes that the abandonment of excessively politicized and ideologized policies both in Russia and in the Western states, which prevents political elites from finding compromises and developing alternative approaches, is the only way to improve the situation in the Eurasian region.